Pengaruh Brand Awareness, Brand Image, Harga, dan Hedonic Terhadap Keputusan Pembelian Iphone (Studi Kasus Mahasiswa di Kota Malang) - Salsabila, Oktaviana Salwa; Arifin, Rois; Utama, Satria Putra (UNIVERSITAS ISLAM MALANG, 2024)
Abstract The research aims to examine the impact of brand awareness, brand image, price, and hedonic on iPhone purchase decisions. This research uses explanatory research with a quantitative approach. The sampling was conducted on 100 college studens in Malang City using the Malhotra formula. The data were analyzed using multiple linear regression measured using SPSS. Test the hypothesis using the t-test and F-test. This research demonstrates that brand awareness, brand image, price, and hedonics collectively exert a significant influence on iPhone purchase decisions. Brand awareness, brand image, and hedonic variables partially influence iPhone purchase decisions, while the price variable does not have a significant effect. Keywords: Brand Awareness, Brand Image, Price, Hedonic, and Purchase Decisions